An Analysis of Women’s Behaviours Stereotypes in ITZY Title Tracks: K-Pop Girl Group Song - Zaniar, Savira (International Journal Labs, 2022)
The Hallyu wave phenomenon becomes a trendsetter in Indonesia lately. Since K-Pop is starting to know spread Hallyu widely, K-Pop music has become a global trend nowadays in the music industry. This study tries to raise awareness of hidden difficulties in a song that we frequently listen to in our daily lives. It also aspires to provide a fresh viewpoint on how gender stereotypes are formed. This research used qualitative methods. Music videos (MVs) and lyrics from all of ITZY's title track songs serve as the study's key data. The information was gathered using the earlier in this section keyword ITZY songs on YouTube. Two theories were used to analyze the data. The first framework is based on Evans and Davies' gender stereotype theory, which consists of eight gender feminine characteristics. Copenhaver's idea of stereotyped gender features provides the second framework. First, the stereotype has been subverted by feminine characteristics that are only seen in passiveness qualities. Women have to express their aspirations and thoughts, and in